The Symbolic Meaning Of The Ruwat Sukerta Tradition In Gemekan Village, Sooko District, Mojokerto Regency - Uqtarina Husni Mu'awanah; Suwardi Endraswara; Doni Dwi Hartanto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The Ruwat Sukerta tradition is a Javanese culture heritage maintained by the community of Gemekan Village, Mojokerto Regency as a ritual to ward off misfortune. Tis study describes the procession, analyzes the symbolic meaning of ubarampe and sesaji, and reveals the embedded cultural values. A descriptive qualitative method was employed through observation, in-depth interviews, and documentation. The procession consists of two stages; preparation and penjamasan. The ubarampe include kembang setaman, sajen sanggan, water from seven springs, jajanan polo pendem gumandul kesampar kesandung, tumpeng pepek, bubur panca warna, and jajanan pasar, each carrying denotative, connotative, and mythical meanings. Culture values identified include safety, life balance, mutual cooperation, respect for ancestors, and spirituality.